Learning Al-Qur’an Hadith Subjects Through Problem Solving Strategy - Cahyani, Regita Vita; Romelah, Romelah; Taufiq, Hadi Nur (Belajea: Jurnal Pendidikan Islam, 2021)
This research aims to find out the study of the Qurâ€™an Hadith through problem solving strategy in MTs Surya Buana Malang. The focus of the problem to be reviewed is: learning planning, learning implementation, and evaluation. This research is qualitative research. This type of research is field research with data collection techniques using interview, observations and documentations. From the results of this study, it can be concluded that the learning of the Qur’an Hadith consists of: 1. Learning planning of the Qur’an Hadith through problem solving strategy consists of syllabus and Learning Implementation Plan. 2. The implementation of the learning of the Qur’an Hadith, opening the lesson by giving important points and reviewing the material, presenting the material then closing the lesson by reviewing, for the implementation of problem solving strategy on the material of the Qur’an Hadith from the results of this study is declared successful. 3. Evaluation of the learning of the Qur’an Hadith, the teacher uses several types of evaluations such as multiple choice, essay or stuffing, and quiz, the teacher behaves ma’fu (tolerance) so that his students can improve the evaluation value.